CHARACTERIZATION OF RADIOACTIVITY FROM PRIMORDIAL RADIONUCLIDES IN THE SOIL OF IKA SOUTH LOCAL GOVERNMENT AREA OF DELTA STATE - ESEKA, KENNETH; MOKOBIA, Chukwuka; MOLUA, COLLINS; Ukpene , Anthony Ossai (FUDMA JOURNAL OF SCIENCES, 2022)
This study presents the characterization of the soil in Ika South Local Government Area of Delta State. It presents radiometric (40K, 238U and 232Th) survey of soil samples collected from some selected towns in Ika South Local Government Area of Delta State, Nigeria using gamma-ray  [NaI(TI)] spectroscopy.Twenty five representative soil samples from five communities (five soil samples each per community) were collected for the study. The average activity concentration of 40K, 238U and 232Th in soil samples from the selected communities was 510.87 Â± 3.068 Bqkg-1, 31.092Â±2.638 Bqkg-1 and 64.662 Â± 2.842 Bqkg-1 respectively. By comparing the obtained average result of soil samples of 40K, 238U and 232Th with UNSCEAR standard, it was observed that the obtained average results of  40K and 232Th exceeded the standard value limit of 400 Bqkg-1 and 30 Bqkg-1  respectively while 238U was less than the standard value limit of 35 Bq/kg-1. The calculated radiological hazard values were lower than the world allowable average standard, except for the annual gonadal dose equivalent and the excess lifetime cancer risk which were above than the world recommended average standard value of 300 mSv/yr and 0.29 x10-3Sv/yr standard in some communities. However, contactwith the soils in these communities will not pose much health hazard problem to man and the environment